2015
DOI: 10.1007/s12522-015-0232-6
|View full text |Cite
|
Sign up to set email alerts
|

Testicular function among testicular cancer survivors treated with cisplatin‐based chemotherapy

Abstract: These findings help to predict whether spermatogenesis will recover and its timing. They may also help clinicians identify and manage TC patients at a higher risk of prolonged azoospermia after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…3 Namekawa et al also reported that the time to recover normospermia was shorter in patients who were treated with less than four cycles of chemotherapy than in those treated with four or more cycles of chemotherapy using Japanese data. 4 In the present study, Hamano et al did not report post-treatment semen parameters and the anticancer treatments in the patients who underwent ICSI. 2 Such information would be useful for identifying patients for whom cryopreservation of sperm should be recommended.…”
Section: Editorial Commentmentioning
confidence: 53%
See 1 more Smart Citation
“…3 Namekawa et al also reported that the time to recover normospermia was shorter in patients who were treated with less than four cycles of chemotherapy than in those treated with four or more cycles of chemotherapy using Japanese data. 4 In the present study, Hamano et al did not report post-treatment semen parameters and the anticancer treatments in the patients who underwent ICSI. 2 Such information would be useful for identifying patients for whom cryopreservation of sperm should be recommended.…”
Section: Editorial Commentmentioning
confidence: 53%
“…Namekawa et al . also reported that the time to recover normospermia was shorter in patients who were treated with less than four cycles of chemotherapy than in those treated with four or more cycles of chemotherapy using Japanese data . In the present study, Hamano et al .…”
mentioning
confidence: 99%
“…The rate of spermatogenesis recovery following various chemotherapeutic agents is highly variable and unpredictable. Highlighting this fact, a recent study found that after an average of 4 cycles of cisplatin only 54% of patients reached normospermia at 3 years post therapy [34]. While another recent study looking at patients receiving various combinations of chemotherapy (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, prednisone) for Hodgkin's lymphoma found that permanent azoospermia was seen even after low doses, and sperm quality was severely compromised in those with resumption of spermatogenesis following treatment [35].…”
Section: Exposuresmentioning
confidence: 99%